Dharma In Vedanta And The Dhammapada - Gurung, Antim (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This paper explores the parallel yet distinct journeys undertaken by Vedanta and the Dhammapada, two profound spiritual traditions rooted in the ancient wisdom of the Bhagavadgita. While their footsteps echo with similarities, a nuanced examination reveals a seemingly divergent trajectory that ultimately converges to crystallize a shared understanding of genuine truth. The Dhammapada, through its profound teachings, enriches the facets of truth, weaving a narrative that complements and strengthens the spiritual evolution outlined in Vedanta. The echoes of Vedantic principles resonate within the spiritual discourse of the Dhammapada, particularly emphasizing the non-dissipation of spiritual essence as expounded in the Bhagavadgita. Central to both traditions is the exploration of cosmopolitanism and the cultivation of nobility in action, untethered by attachments and desires. This exploration transcends the mundane, transforming the seeker from an earthly and material existence into a cosmic being. The thesis contends that, far from leading the seeker astray, this pathfinding virtue liberates one from the shackles of earthly tribulations, allowing the emergence of a broader perspective. The paper theorizes that the mesmerizing words from the Dhammapada and the Bhagavadgita jointly pave a transcendent path, enchanting humanity throughout time. This path, marked by the integration of diverse philosophical tenets, embodies an enduring quest for truth and unity, resonating as a timeless guide for navigating the complexities of human existence.